715. Increase in Reported Respiratory Syncytial Virus Cases Among Adults in the Minneapolis-St. Paul Metropolitan Area, 2014–2018. (26th November 2018) - Como-Sabetti, Kathryn; Bye, Erica; Strain, Anna; McMahon, Melissa; Lynfield, Ruth
Abstract: Background: Respiratory syncytial virus (RSV) is a common cause of respiratory infection, typically causing severe disease in young children. We were interested in evaluating trends of severe RSV infections in adults. Methods: The Minnesota Department of Health conducts active surveillance for laboratory-confirmed RSV in hospitalized patients in the Minneapolis-St. Paul metropolitan area as part of the CDC Emerging Infections Program. Adults (≥18 years) cases identified during the RSV season (10/1–4/30) from 2014 through 2018 were analyzed and surveys of catchment-area hospital laboratories were conducted regarding respiratory virus panel (RVP) testing. Results: Twenty-three catchment area hospitals serve adults. Four hospitals offered RVP during the 2014–2015 and 2015–2016 seasons; eight offered RVP during the 2016–2017 and 2017–2018 seasons. Three hundred and fifty-five cases were identified. Three hundred and nine (87%) were reported from four hospitals where RVP was offered throughout the study period. Case increases were observed at three hospitals; all of these hospitals offered RVP throughout the surveillance period; increases were not observed at hospitals where RVP was added for the 2016–2017 and 2017–2018 seasons. Cases increased from 42 in 2014–2015 to 198 in 2017–2018 ( χ 2 = 125.51, P < 0.01), the proportion of cases reported by year was 12%, 15%, 17% and 56% during consecutive seasons. Cases by age groups over time generally did not differ; however, cases ≥85 years increased from 7% of total cases in 2014–2015 to 19% in 2017–2018 ( χ 2 = 6.14, P = 0.01). Overall, 23% of cases were admitted to the ICU and 7% died during hospitalization. The proportion of ICU admissions and deaths did not change over time. Conclusion: We found an increase in adult RSV hospitalizations from 2014 to 2018, especially among the oldest age group. This increase was observed only at hospitals where RVP testing was offered throughout the surveillance period. It is unclear if this represents a true increase in RSV or a change in testing practices. However, it does illustrate that RSV should be considered as a cause of severe respiratory illness (SARI) in adults, particularly among the elderly. A more systematic approach in identifying the causes of SARI in adults would be informative, particularly as RSV vaccines and antivirals approach licensure. Disclosures: All authors: No reported disclosures.